A century of BCG vaccination: Immune mechanisms, animal models, non-traditional routes and implications for COVID-19 - Singh, Shivani; Saavedra-Avila, Noemi Alejandra; Tiwari, Sangeeta; Porcelli, Steven A. (Frontiers in Immunology, 2022)
Bacillus Calmette-Guerin (BCG) has been used as a vaccine against tuberculosis since 1921 and remains the only currently approved vaccine for this infection. The recent discovery that BCG protects against initial infection, and not just against progression from latent to active disease, has significant implications for ongoing research into the immune mechanisms that are relevant to generate solid host defense against Mycobacterium tuberculosis (Mtb). In this review, we first explore the different components of immunity that are augmented after BCG vaccination. Next, we summarize current efforts to improve the efficacy of BCG through the development of recombinant strains, heterologous prime-boost approaches and the deployment of non-traditional routes. These efforts have included the development of new recombinant BCG strains, and various strategies for expression of important antigens such as those deleted during the M. bovis attenuation process or antigens that are present only in Mtb. BCG is typically administered via the intradermal route, raising questions about whether this could account for its apparent failure to generate long-lasting immunological memory in the lungs and the inconsistent level of protection against pulmonary tuberculosis in adults. Recent years have seen a resurgence of interest in the mucosal and intravenous delivery routes as they have been shown to induce a better immune response both in the systemic and mucosal compartments. Finally, we discuss the potential benefits of the ability of BCG to confer trained immunity in a non-specific manner by broadly stimulating a host immunity resulting in a generalized survival benefit in neonates and the elderly, while potentially offering benefits for the control of new and emerging infectious diseases such as COVID-19. Given that BCG will likely continue to be widely used well into the future, it remains of critical importance to better understand the immune responses driven by it and how to leverage these for the design of improved vaccination strategies against tuberculosis.